2021
DOI: 10.3390/su13095091
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Reports on Comparative Weed Competitiveness of Bangladeshi Monsoon and Winter Rice Varieties under Puddled Transplanted Conditions

Abstract: Weed-competitive rice cultivars, a viable tool for integrated weed management of rice-field weeds, may greatly reduce the weed pressure and excessive dependence on herbicide in controlling weeds. Based on this premise, field experiments were conducted in 2018 and 2019 during the monsoon and winter rice-growing seasons at the Agronomy Field Laboratory of Bangladesh Agricultural University, Bangladesh, to evaluate the weed competitiveness of the selected rice varieties. A total of 42 monsoon and 28 winter rice v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Rice (Oryza sativa L.) constitutes the major staple crop after wheat, which feeds billions of people across the globe and is hence referred to as the global grain [1][2][3]. It is being grown in all habitable continents of the world, owing to its wide adaptability to a wide range of pedo-climatic conditions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) constitutes the major staple crop after wheat, which feeds billions of people across the globe and is hence referred to as the global grain [1][2][3]. It is being grown in all habitable continents of the world, owing to its wide adaptability to a wide range of pedo-climatic conditions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sole legumes probably intercepted more radiation compared to monoculture of maize, while the interception by intercrops remained in between monocultures of legumes and maize which led to higher IA. It was recorded by [1,51,52] that intercrop converted the intercepted radiation into grain yield more efficiently which led to higher land use efficiency by maize-legumes intercropping systems.…”
Section: Discussionmentioning
confidence: 99%
“…An estimate shows that weeds can deprive the crops 47 per cent N, 42 per cent P, 50 per cent K, 39 per cent Ca and 24 per cent Mg of their nutrient uptake. Nitrogen responsive crop species are more competitive under high N-fertilization, but if the associated weed is also responsive to N, it utilizes more of the applied N and no advantage in crop yield may be obtained Echinochloa crus-galli may remove up to 80% of nitrogen from the soil especially in the first half of growing season [35]. Islam et al [36] from his two years of experiment in transplanted rice concluded that, In all seasons (Kharif, Rabi, summer and winter respectively), the same number of weed species was found in the trial field and barnyard grass, E. crus-galli, was the most dominant weed.…”
Section: Nature Of Crop Weed Competetionmentioning
confidence: 99%